The Janus Face of Cathelicidin in Tumorigenesis - Wu, W.K.K.; Sung, J.J.Y.; Cheng, A.S.L.; Chan, F.K.L.; Ng, S.S.M.; To, K.F.; Wang, X.J.; Zhang, L.; Wong, S.H.; Yu, J.; Cho, C.H. (Current Medicinal Chemistry, 2014)
Cathelicidin is a host defense peptide with multiple innate immunity-related functions. Recent findings indicate that cathelicidin is frequently dysregulated in human cancers where it plays a paradoxical yet dominant role in the regulation of tumor malignancy. In this review, the regulation of malignant phenotypes by cathelicidin in relation to the activation of its receptors and intracellular signaling is discussed.
Keywords: signaling